1996
DOI: 10.1007/s004820050048
|View full text |Cite
|
Sign up to set email alerts
|

Substanz P, Somatostatin und monoaminerge Transmitter in der Zerebrospinalflüssigkeit von Patienten mit chronischer idiopathischer Trigeminusneuralgie

Abstract: The etiology of trigeminal neuralgia is unknown, but both peripheral and central causes have been suggested. To investigate the role of central neurochemical mechanisms we measured epinephrine, norepinephrine and their breakdown product, vanilly mandelic acid (VMA), in the cerebrospinal fluid (CSF) of 16 patients (53.3 +/- 8.3 years) suffering from trigeminal neuralgia. As markers for the dopaminergic system, we determined CSF levels of dopamine and its metabolite homovanillic acid (HVA). As a marker for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The central mechanism of TN is related to the damage of dopamine neurons in the substantia striatum, and the decrease of dopamine production leads to the decrease of its anti-injury sensitivity. 9,10 Watanabe et al. 24 believe that the maintenance of neuropathic pain is related to the decrease of dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The central mechanism of TN is related to the damage of dopamine neurons in the substantia striatum, and the decrease of dopamine production leads to the decrease of its anti-injury sensitivity. 9,10 Watanabe et al. 24 believe that the maintenance of neuropathic pain is related to the decrease of dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Strittmatter et al. 9 and Dieb et al. 10 both believe that the central mechanism of TN is related to the damage of dopaminergic neurons in striatum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that neuropathic pain processes probably primarily affect a limited portion of the spinal cord, one could argue that a putative localized excess of SP overspilling into the CSF might be too small to be detectable, and hence not as a single substance sufficient to differ between groups. However, Strittmatter and coworkers found that, compared with patients with nonpainful neurological (mostly neuromuscular) disease, mean CSF‐SP was elevated by 33% ( P < 0.05) in patients with trigeminal neuralgia [34], showing that high CSF‐SP can be demonstrated by lumbar puncture far from the locus of putative overproduction of SP (provided this is not a type I error). When trying to assess different studies of CSF‐SP in human neuropathic pain, it is important to remember that neuropathic pain is not a single entity.…”
Section: Discussionmentioning
confidence: 99%